PELATIHAN MANAJEMEN PENGELOLAAN HOMESTAY DI DESA TETEBATU, KABUPATEN LOMBOK TIMUR - Rizal Kurniansah; Masrun (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The problem that arises in the development of a tourist village in Tetebatu village is the management of homestays that have not run optimally so that the services provided to tourists do not run well and tend to cause complaints from guests. This is based on the competence of human resources in Tetebatu village that cannot be said to be competent as a whole. For this reason, the purpose of this training is to improve the ability of human resources in Tetabatu village to manage their homestays. The methods used are focus group discussion, pre-test, providing material and direct practice by participants about preparing guest rooms, serving guest arrivals and serving food and drinks to guests, and the last method is post-test. Based on the results of the training that has been carried out, in general the training went well and successfully, the participants have been able to carry out direct practice of the training material provided. In addition, based on the results of the evaluation through the post-test to each participant, it was found that the average percentage value of the participants' knowledge was 75% or it could be said that the participants' knowledge was good